2006
DOI: 10.1165/rcmb.2005-0451oc
|View full text |Cite
|
Sign up to set email alerts
|

Gob-5 Contributes to Goblet Cell Hyperplasia and Modulates Pulmonary Tissue Inflammation

Abstract: Gob-5 is a member of the calcium-activated chloride channel family and has been associated with allergic response in mouse models of pulmonary inflammation. Gene expression of Gob-5 has been shown to be induced in allergic airways and has been strongly associated with mucin gene regulation and goblet cell hyperplasia. We investigated the physiologic role of Gob-5 in murine models of pulmonary inflammation using mice deficient in Gob-5. After sensitization and aerosol challenge with ovalbumin (OVA), Gob-5 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 20 publications
4
59
2
Order By: Relevance
“…Another major feature of allergic airway inflammation is the induction of mucus metaplasia (27), and our present studies confirm that OVA sensitization and challenge resulted in enhanced mucus metaplasia, as evaluated by PAS stain ( Figure 4) and expression of IL-13, MUC5ac, and GOB5 (Table 1). GSNO administration did not affect mucus metaplasia in Alum/ OVA mice, but tended to enhance PAS staining in OVA/OVA mice, although this did not reach statistical significance ( Figure 4B; P 5 0.18).…”
Section: Gsno Administration Does Not Suppress Markers Of Allergic Aisupporting
confidence: 84%
“…Another major feature of allergic airway inflammation is the induction of mucus metaplasia (27), and our present studies confirm that OVA sensitization and challenge resulted in enhanced mucus metaplasia, as evaluated by PAS stain ( Figure 4) and expression of IL-13, MUC5ac, and GOB5 (Table 1). GSNO administration did not affect mucus metaplasia in Alum/ OVA mice, but tended to enhance PAS staining in OVA/OVA mice, although this did not reach statistical significance ( Figure 4B; P 5 0.18).…”
Section: Gsno Administration Does Not Suppress Markers Of Allergic Aisupporting
confidence: 84%
“…In agreement, the mRNA abundance of Clca3 (Gob5), which regulates mucus production, and the mucin Muc5ac were lower in OVA/OVAtreated Arg1-KO Tie2 than Arg1-Con mice. Overexpression of Clca3 exacerbates AHR in OVA/OVA-treated mice, whereas downregulation attenuates peak airway pressure (resistance) after methacholine (29,38), strongly suggesting a role for this gene in the development of peripheral responsiveness. On the basis of our observations in sections stained for the presence of collagen and reticular fibers, the improved peripheral lung function could not be caused by less remodeling in OVA/OVA-treated Arg1-KO Tie2 mice compared with Arg1-Con mice.…”
Section: Discussionmentioning
confidence: 99%
“…Its evaluation in blood plasma could represent a useful tool to follow the progression of atherosclerosis [12, 13]. In fact, some studies documented an increased proportion of LDL(–) in patients at high cardiovascular risk [12] and in familial hypercholesterolemia [14, 15], hypertriglyceridemia [16,17,18,19], type 1 and 2 diabetes mellitus [20,21,22,23,24,25,26] and athletes with intense aerobic activity [27]. In end-stage renal disease patients, Ziouzenkova et al [10] reported the presence of LDL(–) in hemodialysis (HD) patients.…”
Section: Introductionmentioning
confidence: 99%